Organic matter affects phosphorus recovery during vivianite crystallization - Changyu Li (IWA Publishing, 2021)
Vivianite crystallization is a promising route for phosphorus (P) recovery from P-rich wastewater. However, organic matter (OM) in wastewater may influence vivianite formation. In this study, the effects of four representative OMs, glucose, bovine serum albumin (BSA), humic acid (HA) and sodium alginate (SA), on P recovery by vivianite were investigated. The results showed that P recovery efficiency was inhibited by HA and SA, declining by 3.7% and 12.1% under HA (100 mg/L) and SA (800 mg/L), respectively. BSA, HA and SA affected the aggregated form of vivianite crystals. Vivianite particle size decreased in the presence of HA and SA. Subsequent mechanistic exploration indicated that the complexation between the OM and Fe2+ was the main cause of P recovery efficiency reduction. The coprecipitation of HA and SA with vivianite could reduce the zeta potential on the crystal surface, resulting in a smaller particle size. The nucleation sites provided by BSA and SA could transfer vivianite from single plate-like agglomerate to multilayer plate-like agglomerate. This study provided a better understanding of P recovery by vivianite from OM-rich wastewater. HIGHLIGHTS Glucose, BSA, HA and SA affected vivianite crystallization from wastewater.; OM might reduce P recovery rate by competition adsorption of Fe2+.; The morphology of vivianite crystals were different under SA and BSA.; Negative correlation presented between OM and Fe/P ratios during crystallization.;